Prevalence of work place violence and its impact on doctors in some Iraqi hospitals - Ali Mousa Al-Mousawi; Riyadh Khudhair Lafta (Journal of the Pakistan Medical Association, 2024)
Objective: To estimate the prevalence of workplace violence and its impact on doctors in hospitals. Method: The cross-sectional study was conducted from August 2021 to January 2022 in Baghdad and Karbala governorates of Iraq, and comprised resident doctors at a number of hospitals. Data was collected using a self-administered questionnaire that focussed on the frequency of exposure to violence, type, source, most common time, and other details about violence as well as its impact on doctors and their careers. Data was analysed using SPSS 23. Results: Of the 1,079 subjects working at 18 participating hospitals and having a mean age 30.0±5.72 years, 567(52.5%) were females and 512(47.5%) were males, while 570(52.8%) were aged <30 years and 509(47.2%) were aged >30 years. Overall, violence exposure was reported by 811(75.2%) subjects; 427(52.6%) females and 384(47.4%) males. Gender was not significantly associated with exposure to violence (p>0.05). Due to missing data, further analysis was limited to 792(97.6%) subjects who faced exposure to workplace violence. In 671(85%) cases, the assaults were nonphysical. However, 110(14%) doctors reported physical attacks and severe consequences. There were 673(85%) of doctors with exposure to violence who expressed their intention to change their job, workplace, or leave the country because of violence. Conclusion: The problem of violence against Iraqi doctors was found to be highly prevalent with a seriously negative impact on the medical professionals. Key Words: Violence, Prevalence, Intention, Malpractice.